Implementasi Packet Filtering Menggunakan Metode Extended Access Control List (ACL) Pada Protokol EIGRP - Muhammad Hafizhan; Moh Iwan Wahyuddin; Ratih Titi Komalasari (STMIK Budi Darma, 2020)
Maintaining security aspects is important for managing network performance so that it can provide optimal services for its users. The difficulty of managing data transmission on a local network (LAN) between two or more divisions, without disrupting data traffic on other divisions, is a major problem for companies. One effort that can be done is to implement an extended access list which is one part of the Access Control List (ACL) method. The extended ACL will be used as packet filtering for each workspace, such as the employee workspace and the manager's workspace. ACL will later run on the EIGRP protocol. the EIGRP protocol will be tested with delay parameters, and the results obtained that by applying the ACL method on EIGRP can provide the availability of networks that have smaller delays with an average of 90.4 ms.